STUDI KAJIAN STRATEGI PROMOSI BISNIS PAKAIAN BERBASIS OFFLINE DAN ONLINE - Icha Tamara Tambunan; Sopyan Handoko; Nur Gita Sari; Andra Pribadi; Dewi Mahrani Rangkuty (Jurnal Riset Ekonomi dan Akuntansi, 2023)
The increasingly fierce competition in the business world has made business people constantly innovate, including in terms of promoting the goods and / or services offered. Along with the times, the promotion of goods and / or services originally carried out through shops, markets or places of business that can be seen and visited directly by consumers can now be done via the internet network through marketplaces or social media. The COVID-19 pandemic that took place globally in 2019-2021 has further increased the role of the marketplace or social media in terms of promoting goods and / or services (online-based promotion). However, the promotion of goods and/or services both offline and online has its own advantages and disadvantages.